Access beyond borders: Linked open data applications on cultural heritage - AKÇA, SÜMEYYE (My University, 2022)
© 2022 The Author(s). Published with license by Taylor & Francis Group, LLC.The main mission of cultural memory institutions is to protect their collections and to provide access to a wider audience. World Wide Web technology offers different tools to fulfill this mission. Among a range of applications, the most effective is the search engines’ search for metadata of collections. However, search engines are not always able to see all sources caused by various problems. Linked data is a publishing technique that uses standard web technologies to associate data with other data and makes them available on the Web. In available literature, it is seen that many memory institutions use Linked Open Data as a solution to the search engine problem with the main motivation of making their collections more accessible. However, these applications are still not at proficient level. In this study, Linked Open Data studies in the available literature were scanned and a process map was created based on these applications. These applications, which especially require technical knowledge and infrastructure, can be confusing for memory institutions that have not yet participated in the process. In this context, it is clear that the process map created as a result of this study will be enlightening for memory institutions. The most important point on the map is that an extensive decision-making mechanism should be formed with the stakeholders before starting the process and the implementation plan should be developed in detail over the problems of existing projects.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Yaşam Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Education; Information Systems, Communication and Control Engineering; Computer Sciences; Information Security and Reliability; Life Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sinirbilim ve Davranış; Sosyal Bilimler Genel; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; TELEKOMÜNİKASYON; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; NEUROSCIENCE & BEHAVIOR; SOCIAL SCIENCES, GENERAL; COMPUTER SCIENCE, INFORMATION SYSTEMS; TELECOMMUNICATIONS; EDUCATION & EDUCATIONAL RESEARCH; Bilgi sistemi; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; İnsan Bilgisayar Etkileşimi; Bilgisayar Ağları ve İletişim; Information Systems; Physical Sciences; Social Sciences & Humanities; Human-Computer Interaction; Computer Networks and Communications; Cultural heritage; linked data; linked open data; metadata; metadata schemas